Role of Interfacial Water and Applied Potential on Friction at Au(111) Surfaces - Pashazanusi, Leila; Kristiansen, Kai; Li, Shaowei; Tian, Yu; Pesika, Noshir S. (Frontiers in Mechanical Engineering, 2019)
The tribological properties between an AFM tip and a Au(111) surface in an aqueous environment is influenced by an applied electrical potential. Using lateral force microscopy, we measure the resulting friction force, while simultaneously applying a predetermined electrical potential on the Au surface via a three-electrode setup. Applying a positive potential to the Au surface forms an interfacial water layer at the Au/electrolyte interface, which sharply increases friction. However, when an anodic potential is applied, lower friction forces are measured. The potential dependent friction is observed on ultra-smooth gold surfaces as well as Au surfaces with larger roughness. An increase in the ionic strength of the electrolyte is found to lower friction. The use of an aqueous NaOH solution is found to lower the critical potential at which the friction sharply increases. Normal force curves are also measured as a function of approach velocity. The normal force linearly increases as the approach velocity increases in agreement with a drainage model. These results provide valuable insight into the effect of applied electrical potentials on the properties of water at charged surfaces and can potentially impact a wide range of fields including tribology, micro-electro-mechanical systems (MEMS), energy storage devices, fuel cells and catalysis.